ANALISIS ISI KUANTITATIF BERITA PIDATO KENEGARAAN PRESIDEN JOKO WIDODO PERIODE II PADA KRJogja.com dan Solopos.com - Laila Nilasari; Lukas Maserona Sarungu (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
The research entitled Quantitative Content Analysis of President Joko Widodo's Period II State Speech News on KRJogja.com and Solopos.com examines how local mass media frame Nawacita priorities in the news of the President's state speech in the second period of his administration. The analysis was conducted using a descriptive method with a quantitative content analysis approach to ten online news published by KRJogja.com and Solopos.com throughout 2019-2024. Each news story was coded based on the Nawacita category and analyzed with descriptive statistics to identify the most prominent themes. The results showed that the Nawacita “Improving the Quality of Indonesian Human Beings” dominated the news, especially in 2022, followed by “Equitable and Fair Development” and “Productive Economic Structure”. KRJogja.com tends to give a larger portion to national development issues, while Solopos.com is more selective to suit the needs of local audiences. This finding confirms the role of local media in agenda setting, but at the same time shows a tendency to highlight certain issues. The research recommendations encourage the government to strengthen synergies with local media and the media to increase the diversity of Nawacita coverage to broaden public understanding. Keywords: Quantitative Content Analysis, State Speech, Nawacita, Agenda Setting, Local Media